IMPLEMENTING DEEP LEARNING THROUGH THE DEVELOPMENT OF ECO-PESANTREN AS A SCHOOL CULTURE AT PPM BAITUSSALAM - Prihatin, Novianto Ari; Novianto, Victor (Jurnal Sosialita, 2025)
This study aims to find out: (1) To describe the implementation of Deep Learning in the management of Eco Pesantren. (2) To describe and analyse the potential of Eco Pesantren program at PPM Baitussalam Prambnanan. (3) To describe the development of Eco Pesantren at PPM Baitussalam. This research method uses qualitative methods. The research object was carried out at PPM Baitussalam. The target subjects of the research were the head of the Pondok, the principal, the person in charge of the Pondok Kerumahtanggan section, and the students. The data collection techniques used were observation, interview, and documentation. The data analysis technique used was qualitative data analysis of the Miles and Huberman model consisting of data reduction, data presentation, and conclusion drawing. The results showed that first, Eco Pesantren is an environment-based pesantren education programme that is in line with the concept of deep learning in involving students in pesantren activities. Second, PPM Baitussalam has potentials that can be developed for the Eco Pesantren program, including the pesantren's business charities (minimarket, canteen, student organisation, catfish farm, vegetable and fruit farm). Third, the potential for developing school culture at PPM Baitussalam can be in the form of integrated waste management. Organic waste in the form of leftover consumption and restaurant waste can be reprocessed into organic catfish feed so as not to produce disturbing waste. Non-organic waste can be utilised as a means for students' economic literacy by creating a system like a waste bank. The use of Smart Cards in the financial transaction activities of students can function like an ATM that will be directly integrated with the Smartsystem at the financial centre of the boarding school. With the management of the Eco Pesantren, it is expected that sustainable environmental management will be created. Keywords: Implementation, Deep Leaning, Eco Pesantren, PPM Baitussalam